Growth of ferromanganese crusts on bioturbated soft substrate, Tropic Seamount, northeast Atlantic ocean - Kfouri, Luciana Ortiz; Millo, Christian; Lima, Amanda Estela de; Silveira, Carla Semiramis; Sant'Anna, Lucy Gomes; Marino, Egidio; González Sanz, Francisco Javier; Sayeg, Isaac Jamil; Hein, James R.; Jovane, Luigi; Bernardini, Simone; Lusty, Paul A.J.; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2021)
[EN] The growth of ferromanganese (FeMn) crusts on soft substrates is uncommon. FeMn crusts generally accrete on hard-rock surfaces, where sedimentation rates are low and the rocks free of sediment cover. Here we use X-ray Powder Diffraction, Fourier Transform-Infra Red spectroscopy, Raman spectroscopy, X-ray Computed Micro-Tomography, Scanning Electron Microscopy and Particle Size Distribution analysis to investigate FeMn crusts associated with a porous, weakly consolidated, and bioturbated siltstone consisting mainly of authigenic palygorskite. FeMn crusts occur both on the surface of the siltstone and as FeMn lining and/or infilling of bioturbation burrows. Our results show that variations in the water redox conditions lead to a micrometric alternation of hydrogenetic vernadite and diagenetic todorokite and asbolane. These variations affected the oxidation state of Mn, which increased during the diagenetic formation of todorokite. The mineralogy of the FeMn oxides lining bioturbation traces is similar to that of the crusts growing on the siltstone, suggesting that they are genetically related and probably contemporaneous. Bioturbation burrows lined by FeMn oxides are unfilled (the siltstone porosity is 5–10%) or filled by bioclastic carbonate sediment. The soft siltstone possibly resulted from the alteration of volcaniclastic-pyroclastic sediments, forming authigenic palygorskite. Bioturbation of the sediment by burrowing organisms lead to seawater percolation, followed by hydrogenetic or diagenetic precipitation of FeMn linings under oxic/suboxic conditions within the burrows. These findings emphasize the importance of weakly-consolidated substrates with bioturbation cavities for the formation of marine polymetallic deposits. Funding: This work was supported by the Natural Environment Research Council (NERC, grant number NE/MO11151/1) and by the Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP, grant number 2014/50820-7). The Program Mobilidade Santander gave financial support to C. Millo. The ...